Is the LICOX® PtO2 system reliable for monitoring of free flaps? Comparison between two cohorts of patients. Issue 5 (4th December 2018) - Arnež, Zoran Marij; Ramella, Vittorio; Papa, Giovanni; Novati, Federico Cesare; Manca, Elisa; Leuzzi, Sara; Stocco, Chiara
Abstract : Background: Licox® PtO2 is a minimally invasive monitoring system for continuous measurement of tissue oxygen tension in all types of free tissue transfers. Our study compares two consecutive series of patients undergoing microsurgical reconstruction monitored with standard clinical bedside surveillance and with the Licox® PtO2 system regarding flap loss and flap salvage, the sensitivity, specificity, and cost‐effectiveness. Methods: We performed a longitudinal observational prospective study of all patients undergoing microsurgical reconstructions between 2016 and 2017. Group 1 included 43 patients that underwent standard clinical bedside postoperative flap monitoring whereas group 2 included 44 consecutive patients also monitored with Licox® PtO2 system. Flap complications such as return to theater for vascular compromise, partial and total flap loss and flap salvage rate were analyzed. Results: We recorded no significant difference between the two groups regarding the rate of vascular complications ( P = .31), return to the theater ( P = .31), flap salvage ( P = .9), partial and total flap loss ( P = .36 and P = .49, respectively). When analyzing the Licox® PtO2 system monitoring group, we documented six false‐positive results (13.6%) and 0 false negatives with an accuracy of 0.86, a sensibility of 1.00, and a specificity of 0.85. Conclusions: This is the first study that provides statistical data about the comparison of postoperative free flap monitoring by standard clinical bedside method and Licox® PtO2 system. For the monitoring of buried flaps, the Licox® PtO2 monitoring can be used only as a supplement to other systems. Its use, compared to near‐infrared spectroscopy or clinical bedside monitoring, was not found cost‐efficient.